Oxygen vacancy-rich cobalt oxide / ferroferric oxide composite catalyst and preparation method and application thereof
By preparing an oxygen-enriched vacancies cobalt oxide/ferrous tetraoxide composite catalyst, the problem of insufficient adsorption and activation capacity of existing cobalt oxide catalysts for nitrates is solved, and high-efficiency electrocatalytic reduction of nitrates is achieved and the selectivity and reaction rate of ammonia synthesis are improved.
Patent Information
- Application Number
- CN202411696199.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-03-14
AI Technical Summary
The existing cobalt oxide catalysts have poor adsorption and activation ability of nitrates, resulting in insufficient reactivity and selectivity during the electrocatalytic reduction of nitrates to ammonia.
The preparation method of oxygen-rich vacancies cobalt oxide/ferrooxide composite catalyst is adopted, and the oxygen-rich vacancies are mixed with polyol, iron salt and chelating agent are added for coordination reaction, and the reaction is carried out under solvent-heat conditions to form an oxygen-rich vacancies.
The catalyst's adsorption and activation ability of nitrates was significantly enhanced, and the selectivity and reaction rate of synthesis of ammonia were improved. The ammonia production rate was 1.09 mmol h-1cm-2, the Faraday current efficiency was 82.22%, and the ammonia nitrogen selectivity was 75.2%.
Smart Images

Figure CN119608164A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of electrocatalysis and relates to an oxygen-rich vacancy cobalt oxide / ferroferric oxide composite catalyst and a preparation method and application thereof. Background Art
[0002] Ammonia nitrogen is a resource-based multifunctional chemical with an increasing demand in the manufacturing industries of synthetic fertilizers, plastics, explosives and fibers. At present, the global ammonia nitrogen production process mainly relies on the Haber-Bosch process. However, the ammonia nitrogen conversion rate of this process is low (10%), and the energy consumption is high (7.7-10.1 kWh kg -1 ), it is difficult to meet the requirements of clean production. At the same time, nitrate pollution caused by over-fertilization and industrial emissions is affecting the global ecological environment and biological health. How to treat high-concentration nitrate wastewater has become an urgent problem to be solved. In recent years, electrocatalytic nitrate reduction to ammonia (eNO3 - Electrocatalytic reduction of nitrate to ammonia (ER) has attracted wide attention due to its mild reaction conditions and compatibility with renewable electricity, and is expected to solve both energy and environmental crises. The process of electrocatalytic reduction of nitrate to ammonia involves nitrogen-containing species with different valence states from +5 to -3, and the molecular orbital of the nitrate ion contains a delocalized large π bond, which has strong stability and leads to slow reaction kinetics. Therefore, the development of catalysts with high reactivity to nitrate and high selectivity to ammonia nitrogen is a research focus in this field.
[0003] At present, the catalysts used for the electrocatalytic reduction of nitrate to ammonia are mainly cobalt-based catalysts, such as cobalt oxides (including CoO and Co3O4). However, their adsorption and activation abilities for nitrate are still relatively poor, and they still have defects such as poor reaction activity and poor selectivity when used for the electrocatalytic reduction of nitrate to ammonia. In this regard, some researchers have proposed a method for preparing a composite catalyst by coating other metal oxides on the surface of cobalt oxide. Specifically, other metal oxides are coated on the surface of cobalt oxide by a sol-gel method, a high-temperature calcination method, and an electrochemical deposition method. However, since it is difficult to change the crystal structure of the metal oxide precursor in the above-mentioned preparation method, it is difficult to produce low-valent metal oxides, resulting in the inability to form oxygen vacancies or the concentration of oxygen vacancies in these composite catalysts is very low, and it is difficult to enhance the adsorption and activation of nitrates, making it difficult for these composite catalysts to achieve efficient electrocatalytic reduction of nitrates. In a more serious situation, in the above-mentioned preparation method, the Ni precursor is coated on the surface of the Co precursor, and then the Co3O4@NiO composite catalyst is prepared by annealing. Since the hydrogen evolution active phase NiO is exposed on the catalyst surface, the catalyst has a low selectivity for nitrate reduction reaction. In addition, some researchers have proposed a method for preparing Fe3O4 / CoO composite nanoparticles, which first synthesizes Fe3O4 nanomagnetic particles, and then uses Fe3O4 nanomagnetic particles as raw materials to coat CoO on the surface of Fe3O4 nanomagnetic particles through a hydrothermal reaction to obtain Fe3O4 / CoO composite nanoparticles with a core-shell structure. Although the core-shell structure formed by using CoO to coat Fe3O4 can protect the Fe3O4 nanomagnetic particles, the Fe3O4 / CoO composite nanoparticles cannot achieve efficient electrocatalysis of nitrates. The reasons are: (a) CoO's adsorption and activation ability for nitrates is significantly inferior to Co3O4; (b) Fe3O4 is coated inside, which makes it difficult to utilize the oxygen vacancies in the composite nanoparticles, and thus it is difficult to enhance the adsorption and activation of nitrates; (c) More cobalt active sites are exposed on the catalyst surface, which easily leads to the electrode surface reaction being more inclined to hydrogen evolution reaction rather than nitrate reduction reaction.
[0004] Therefore, obtaining a cobalt oxide composite catalyst that can enhance the adsorption and activation ability of nitrate is of great significance for the efficient electrocatalytic reduction of nitrate and the synthesis of ammonia while effectively treating nitrate wastewater. Summary of the invention
[0005] The technical problem to be solved by the present invention is to overcome the deficiencies of the prior art and provide an oxygen-rich vacancy cobalt oxide / ferroferric oxide composite catalyst capable of enhancing the adsorption and activation capabilities of nitrates, and a preparation method and application thereof.
[0006] In order to solve the above technical problems, the present invention adopts the following technical solutions.
[0007] A method for preparing an oxygen-rich vacancy cobalt oxide / ferroferric oxide composite catalyst comprises the following steps:
[0008] S1, mixing Co3O4 nanoparticles with polyols, dispersing by ultrasonication, adding iron salt, dissolving, adding a chelating agent for coordination reaction, and obtaining a mixed solution;
[0009] S2. The mixed solution is subjected to a solvothermal reaction with a pH regulator to obtain an oxygen-rich vacancy cobalt oxide / ferroferric oxide composite catalyst.
[0010] The above preparation method is further improved in that the mass ratio of the iron salt to the Co3O4 nanoparticles is 1 to 14:1.
[0011] The above preparation method is further improved in that the iron salt is ferric chloride.
[0012] The above preparation method is further improved in that the ratio of the Co3O4 nanoparticles to the polyol is 9 mg:4 mL.
[0013] The above preparation method is further improved, wherein the polyol is at least one of ethylene glycol, diethylene glycol, and propylene glycol.
[0014] The above preparation method is further improved in that the mass ratio of the chelating agent to the Co3O4 nanoparticles is 40:3.
[0015] The above preparation method is further improved, wherein the chelating agent is at least one of trisodium citrate, sodium ethylenediaminetetraacetate and sodium tartrate.
[0016] The above preparation method is further improved in that the mass ratio of the pH regulator to the Co3O4 nanoparticles is 20:9.
[0017] The above preparation method is further improved, wherein the pH regulator is at least one of sodium acetate, ammonium hydroxide, sodium carbonate, sodium phosphate and sodium borate.
[0018] The above preparation method is further improved in that the temperature of the solvent thermal reaction is 200° C. and the time of the solvent thermal reaction is 10 hours.
[0019] The above preparation method is further improved, wherein the Co3O4 nanoparticles are prepared by calcining a cobalt-based metal organic framework; the calcination is carried out in an air atmosphere; the heating rate during the calcination process is 2.5°C / min; the calcination temperature is 550°C; and the calcination time is 4h.
[0020] The above-mentioned preparation method is further improved, wherein the cobalt-based metal organic framework is a ZIF-67 material; the preparation method of the ZIF-67 material comprises the following steps: dissolving 2-methylimidazole and cobalt nitrate in methanol respectively to obtain a 2-methylimidazole solution and a cobalt nitrate solution respectively; adding the 2-methylimidazole solution to the cobalt nitrate solution, stirring, standing, centrifuging, washing, and drying to obtain the ZIF-67 material.
[0021] The above preparation method is further improved in that the molar ratio of cobalt nitrate to 2-methylimidazole is 1-8:1.
[0022] As a general technical concept, the present invention also provides an oxygen-vacancy-rich cobalt oxide / ferroferric oxide composite catalyst, which is prepared by the above-mentioned preparation method.
[0023] The above-mentioned oxygen-rich vacancy cobalt oxide / ferroferric oxide composite catalyst is further improved, wherein the oxygen-rich vacancy cobalt oxide / ferroferric oxide composite catalyst comprises cobalt oxide nanoparticles; the cobalt oxide nanoparticles comprise Co3O4 nanoparticles and CoO nanoparticles; and Fe3O4 nanoparticles are grown on the surface of the cobalt oxide nanoparticles.
[0024] The above oxygen-rich vacancy cobalt oxide / ferroferric oxide composite catalyst is further improved in that the mass ratio of cobalt to iron in the oxygen-rich vacancy cobalt oxide / ferroferric oxide composite catalyst is 0.2-5.0:1.
[0025] As a general technical concept, the present invention also provides an application of the above-mentioned oxygen-vacancy-rich cobalt oxide / ferroferric oxide composite catalyst in the electrocatalytic reduction of nitrate to synthesize ammonia.
[0026] The above application, further improved, comprises the following steps:
[0027] (1) preparing a catalytic electrode by using an oxygen-vacancy-rich cobalt oxide / ferroferric oxide composite catalyst;
[0028] (2) constructing an electrocatalytic device using the catalytic electrode as the working electrode;
[0029] (3) The nitrate wastewater is introduced into an electrocatalytic device for electrocatalytic reduction reaction, thereby completing the treatment of the nitrate wastewater and collecting ammonia gas.
[0030] The above application is further improved, in step (1), the preparation method of the catalytic electrode comprises the following steps: mixing the oxygen-rich vacancy cobalt oxide / ferroferric oxide composite catalyst with a mixed solution of water, isopropanol and naphthol, ultrasonically dispersing, drop-coating on a conductive substrate, and drying to obtain a catalytic electrode; the ratio of the oxygen-rich vacancy cobalt oxide / ferroferric oxide composite catalyst to the mixed solution of water, isopropanol and naphthol is 5 mg:1 mL; the volume ratio of water, isopropanol and naphthol in the mixed solution of water, isopropanol and naphthol is 13:6:1; the ultrasonic dispersion time is 1 hour; the conductive substrate is conductive carbon paper; and the drying temperature is 50°C.
[0031] The above application is further improved, in step (3), the concentration of nitrate in the nitrate wastewater is 0.01 mol / L to 0.1 mol / L; the nitrate is potassium nitrate; potassium hydroxide is added to the nitrate wastewater; the concentration of potassium hydroxide in the nitrate wastewater is 0.1 mol / L; the electrocatalytic reduction reaction is carried out at an electrode potential of -0.3 V to -1.1 V relative to the reversible hydrogen electrode; the time of the electrocatalytic reduction reaction is 0.5 h.
[0032] Compared with the prior art, the advantages of the present invention are:
[0033] (1) In view of the defects of existing cobalt oxide catalysts such as poor adsorption and activation ability for nitrate, the present invention creatively provides a method for preparing an oxygen-rich vacancy cobalt oxide / ferroferric oxide composite catalyst, wherein Co3O4 nanoparticles are used as a precursor, first mixed with a polyol, and then the Co3O4 nanoparticles are evenly dispersed by ultrasonic dispersion, and then iron salt is added and dissolved to form a mixed solution in which the Co3O4 nanoparticles and the iron salt are evenly dispersed. On this basis, a chelating agent is added to react with the chelating agent to react with the iron salt (iron ions) first, and then the iron ions are evenly dispersed on the Co3O4 nanoparticles by the chelating agent. At the same time, precipitation due to hydrolysis of the iron salt can be avoided. Finally, When a pH regulator is added to carry out a solvothermal reaction, on the one hand, under the joint action of the solvent and the chelating agent, more Fe3O4 nanoparticles can be grown in situ on the Co3O4 nanoparticles, and the Fe3O4 nanoparticles have no obvious stacking, which makes the catalyst surface have more active sites, which is beneficial to increase the content of oxygen vacancies in the catalyst, thereby enhancing the adsorption and activation of the catalyst to nitrate. On the other hand, under the joint action of the solvent and the pH regulator, part of the trivalent iron can be reduced to divalent iron, and with the joint action of the pH regulator, part of the Co3O4 can be reduced to CoO, thereby further improving the adsorption and activation ability of the catalyst to nitrate under the joint action of Co3O4 and CoO. More importantly, in the catalyst prepared by the present invention, the Co3O4 nanoparticles not only serve as the precursor of the CoO nanoparticles, but also serve as the carrier of the Fe3O4 nanoparticles, so that the nanoparticles in the catalyst are more evenly dispersed and have a higher specific surface area. In addition, the Fe3O4 nanoparticles grow on the surface of the nanoparticles, so that the composite catalyst has more oxygen vacancies, which can promote the selectivity of the catalyst for nitrate reduction. At the same time, the Fe3O4 nanoparticles are used as magnetic nanoparticles, so that the composite catalyst has certain magnetism and is easy to recover. It can be seen that under the joint action of Co3O4 and CoO, the catalyst prepared by the present invention has higher redox activity and adsorption capacity, which is beneficial to improving the catalyst's ability to convert nitrate. In addition, under the joint action of Co3O4, CoO and Fe3O4, the conductivity is significantly enhanced, so that the catalyst prepared by the present invention can enhance the transfer of electrons and the adsorption and activation of reactants. Compared with the cobalt oxide catalyst prepared by the conventional method, the oxygen-vacancy-rich cobalt oxide / ferroferric oxide composite catalyst prepared by the present invention contains abundant oxygen vacancies, which can not only significantly enhance the adsorption and activation ability of nitrate, but also significantly improve the selectivity and reaction rate of synthetic ammonia. The ammonia production rate of the oxygen-vacancy-rich cobalt oxide / ferroferric oxide composite catalyst of the present invention is 1.09 mmol h -1 cm -2, the Faraday current efficiency is 82.22%, and the ammonia nitrogen selectivity is 75.2%, while the ammonia nitrogen selectivity of conventional cobalt oxide catalysts is 40%-50%. The oxygen-vacancy-rich cobalt oxide / ferroferric oxide composite catalyst of the present invention has the characteristics of being rich in oxygen vacancies, and can enhance the adsorption and activation ability of nitrates, so that efficient electrocatalytic reduction of nitrates can be achieved, and at the same time, it also has very excellent stability, and has important application value in nitrate wastewater treatment and ammonia synthesis.
[0034] (2) In the preparation method of the present invention, the mass ratio of iron salt to Co3O4 nanoparticles is also optimized to 1 to 14:1. By optimizing the amount of iron salt, it is beneficial to increase the content of oxygen vacancies in the catalyst, so that the content of oxygen vacancies in the catalyst of the present invention is higher. In particular, the content of -OH adsorbed on the catalyst surface increases with the increase of oxygen vacancy concentration. This is because oxygen vacancies can form dangling bonds at metal-oxygen sites, promoting the formation of M-OH on the catalyst surface.
[0035] (3) In the preparation method of the present invention, the cobalt-based metal organic framework is used as a raw material, and irregularly shaped Co3O4 nanoparticles are prepared by calcination. Using it as a raw material is conducive to preparing a catalyst with more active sites and higher oxygen vacancy content.
[0036] (4) The present invention also provides an oxygen-rich vacancy cobalt oxide / ferroferric oxide composite catalyst including cobalt oxide nanoparticles, wherein the cobalt oxide nanoparticles include Co3O4 nanoparticles and CoO nanoparticles, and Fe3O4 nanoparticles grow on the surface of the cobalt oxide nanoparticles; at the same time, the mass ratio of cobalt element to iron element in the oxygen-rich vacancy cobalt oxide / ferroferric oxide composite catalyst of the present invention is also optimized to be 0.2 to 5.0:1, and the selectivity of the catalyst for nitrate reduction reaction can be optimized by regulating the ratio of cobalt to iron in the composite catalyst. In the present invention, adding appropriate cobalt active sites can promote the hydrogenation reaction of nitrate, but excessive cobalt sites will enhance the hydrogen evolution reaction, thereby inhibiting nitrate reduction.
[0037] (5) The present invention also provides an application of an oxygen-rich vacancy cobalt oxide / ferroferric oxide composite catalyst in the electrocatalytic reduction of nitrate to synthesize ammonia. By preparing the oxygen-rich vacancy cobalt oxide / ferroferric oxide composite catalyst into a catalytic electrode and using it as a working electrode to construct an electrocatalytic device, efficient electrocatalysis of nitrate can be achieved, and nitrate can be quickly reduced to ammonia. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] In order to make the purpose, technical solution and advantages of the embodiments of the present invention more clear, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the accompanying drawings in the embodiments of the present invention.
[0039] Figure 1 The oxygen-rich cobalt oxide / ferroferric oxide composite catalyst (CoO X / Fe3O4), XRD patterns of the Co3O4 catalyst (Co3O4) prepared in Comparative Example 1, and the Fe3O4 catalyst (Fe3O4) prepared in Comparative Example 2.
[0040] Figure 2 The oxygen-rich cobalt oxide / ferroferric oxide composite catalyst (CoO X / Fe3O4) SEM image.
[0041] Figure 3 The oxygen-rich cobalt oxide / ferroferric oxide composite catalyst (CoO X / Fe3O4), the Co3O4 catalyst prepared in Comparative Example 1 (Co3O4), and the Fe3O4 catalyst prepared in Comparative Example 2 (Fe3O4).
[0042] Figure 4 The oxygen-rich cobalt oxide / ferroferric oxide composite catalyst (CoO X / Fe3O4), EPR patterns of the Co3O4 catalyst (Co3O4) prepared in Comparative Example 1, and the Fe3O4 catalyst (Fe3O4) prepared in Comparative Example 2.
[0043] Figure 5 The oxygen-rich cobalt oxide / ferroferric oxide composite catalyst (CoO X / Fe3O4), Co3O4 catalyst (Co3O4) and Fe3O4 catalyst (Fe3O4) at different potentials.
[0044] Figure 6 The oxygen-rich cobalt oxide / ferroferric oxide composite catalyst (CoO X / Fe3O4), Co3O4 catalyst (Co3O4) and Fe3O4 catalyst (Fe3O4) at different potentials.
[0045] Figure 7 The oxygen-rich cobalt oxide / ferroferric oxide composite catalyst (CoO X A comparison chart of the Faraday current efficiency and ammonia production rate results of the catalytic electrode made of / Fe3O4) for nitrate wastewater with different concentrations at a potential of -0.9V.
[0046] Figure 8The oxygen-rich cobalt oxide / ferroferric oxide composite catalyst (CoO X / Fe3O4) under different electrocatalytic reduction reaction conditions.
[0047] Fig. 9 The oxygen-rich cobalt oxide / ferroferric oxide composite catalyst (CoO X / Fe3O4) on the recycling treatment effect of nitrate wastewater. DETAILED DESCRIPTION
[0048] The present invention is further described below in conjunction with the accompanying drawings and specific preferred embodiments of the specification, but the protection scope of the present invention is not limited thereby. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0049] The "range" disclosed in the present invention can be defined in the form of a lower limit and an upper limit, and a given range is defined by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundaries of a particular range. The range defined in this way can be inclusive or exclusive of the end values, and any end value can be included or excluded independently, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a range. For example, if a range of 60 to 120 and 80 to 110 is listed for a specific parameter, it is understood that a range of 60 to 110 and 80 to 120 is also expected. In addition, if the minimum range values 1 and 2 are listed, and if the maximum range values 3, 4 and 5 are also listed, the following ranges can all be expected: 1 to 3, 1 to 4, 1 to 5, 2 to 3, 2 to 4 and 2 to 5. In the present invention, unless otherwise specified, the numerical range "a to b" represents an abbreviation of any real number combination between a and b, wherein a and b are both real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" have been listed in this article, and "0-5" is just an abbreviation of these numerical combinations.
[0050] In the present invention, "plurality", "multiple" and the like, unless otherwise specified, refer to a number greater than or equal to 2. For example, "one or more" means one or greater than or equal to two.
[0051] If not otherwise specified, all embodiments and optional embodiments of the present invention can be combined with each other to form a new technical solution.
[0052] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment or implementation of the present invention. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments. Reference to "implementations" herein has a similar understanding.
[0053] Those skilled in the art will appreciate that, in the methods of various embodiments or examples, the order in which each step is written does not mean a strict order of execution and does not constitute any limitation on the implementation process, and the detailed order of execution of each step should be determined by its function and possible internal logic. If there is no special explanation, all steps of the present invention can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may also include step (c), indicating that step (c) may be added to the method in any order, for example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0054] In the present invention, unless otherwise specified, A (such as B) means that B is a non-limiting example of A, and it can be understood that A is not limited to B.
[0055] In the present invention, "optionally", "optional", and "optional" mean optional or dispensable, that is, any one of the two parallel solutions of "yes" or "no". If multiple "options" appear in a technical solution, unless otherwise specified and there is no contradiction or mutual restriction, each "option" is independent.
[0056] In the first aspect, in view of the defects of existing cobalt oxide catalysts such as poor adsorption and activation ability for nitrates, based on this, the present invention provides a method for preparing an oxygen-rich vacancy cobalt oxide / ferroferric oxide composite catalyst, comprising the following steps:
[0057] S1, mixing Co3O4 nanoparticles with polyols, dispersing by ultrasonication, adding iron salt, dissolving, adding a chelating agent for coordination reaction, and obtaining a mixed solution;
[0058] S2. The mixed solution is subjected to a solvothermal reaction with a pH regulator to obtain an oxygen-rich vacancy cobalt oxide / ferroferric oxide composite catalyst.
[0059] In the preparation method of the present embodiment, Co3O4 nanoparticles are used as a precursor, which is first mixed with a polyol, and the Co3O4 nanoparticles are uniformly dispersed by ultrasonic dispersion. Iron salt is added and dissolved to form a mixed solution in which Co3O4 nanoparticles and iron salt are uniformly dispersed. On this basis, a chelating agent is added to undergo a coordination reaction, and under the action of the chelating agent, it is ensured that the iron salt (iron ions) first undergo a coordination reaction with the chelating agent, and the iron ions are uniformly dispersed on the Co3O4 nanoparticles through the chelating agent, while also being able to avoid precipitation due to hydrolysis of the iron salt. Finally, a pH regulator is added to perform a solvothermal reaction. On the one hand, in the presence of a solvent and a chelating agent, the iron salt (iron ions) is subjected to a coordination reaction with the chelating agent. The iron ions are uniformly dispersed on the Co3O4 nanoparticles. Under the action of the solvent, more Fe3O4 nanoparticles can be grown in situ on the Co3O4 nanoparticles, and the Fe3O4 nanoparticles have no obvious stacking, which makes the catalyst surface have more active sites, which is beneficial to increase the content of oxygen vacancies in the catalyst, thereby enhancing the adsorption and activation of the catalyst to nitrate. On the other hand, under the joint action of the solvent and the pH regulator, part of the trivalent iron can be reduced to divalent iron, and with the joint action of the pH regulator, part of the Co3O4 can be reduced to CoO, thereby further improving the adsorption and activation ability of the catalyst to nitrate under the joint action of Co3O4 and CoO. More importantly, in the catalyst prepared by the present invention, the Co3O4 nanoparticles not only serve as the precursor of the CoO nanoparticles, but also serve as the carrier of the Fe3O4 nanoparticles, so that the nanoparticles in the catalyst are more evenly dispersed and have a higher specific surface area. In addition, the Fe3O4 nanoparticles grow on the surface of the nanoparticles, so that the composite catalyst has more oxygen vacancies, which can promote the selectivity of the catalyst for nitrate reduction. At the same time, the Fe3O4 nanoparticles are used as magnetic nanoparticles, so that the composite catalyst has certain magnetism and is easy to recover. It can be seen that under the joint action of Co3O4 and CoO, the catalyst prepared by the present invention has higher redox activity and adsorption capacity, which is beneficial to improving the catalyst's ability to convert nitrate. In addition, under the joint action of Co3O4, CoO and Fe3O4, the conductivity is significantly enhanced, so that the catalyst prepared by the present invention can enhance the transfer of electrons and the adsorption and activation of reactants. Compared with the cobalt oxide catalyst prepared by the conventional method, the oxygen-vacancy-rich cobalt oxide / ferroferric oxide composite catalyst prepared by the present invention contains abundant oxygen vacancies, which can not only significantly enhance the adsorption and activation ability of nitrate, but also significantly improve the selectivity and reaction rate of synthetic ammonia. The ammonia production rate of the oxygen-vacancy-rich cobalt oxide / ferroferric oxide composite catalyst of the present invention is 1.09 mmol h -1 cm -2, the Faraday current efficiency is 82.22%, and the ammonia nitrogen selectivity is 75.2%, while the ammonia nitrogen selectivity of conventional cobalt oxide catalysts is 40%-50%. The oxygen-vacancy-rich cobalt oxide / ferroferric oxide composite catalyst of the present invention has the characteristics of being rich in oxygen vacancies, and can enhance the adsorption and activation ability of nitrates, so that efficient electrocatalytic reduction of nitrates can be achieved, and at the same time, it also has very excellent stability, and has important application value in nitrate wastewater treatment and ammonia synthesis.
[0060] In some embodiments, the mass ratio of the iron salt to the Co3O4 nanoparticles is 1 to 14:1. As an example, the mass ratio of the iron salt to the Co3O4 nanoparticles may be 1:1, 2:1, 3:1, 4:1, 4.5:1, 5:1, 6:1, 7:1, 8:1, 9:1, 10:1, 11:1, 12:1, 13:1, 14:1, or may be in the range formed by any two of the above-mentioned point values as end values. Optionally, the mass ratio of the iron salt to the Co3O4 nanoparticles is 3 to 10:1. In the preparation method of the present invention, by optimizing the mass ratio of the iron salt to the Co3O4 nanoparticles to 1 to 14:1, it is beneficial to increase the content of oxygen vacancies in the catalyst, so that the content of oxygen vacancies in the catalyst of the present invention is higher. In particular, the content of -OH adsorbed on the catalyst surface increases with the increase of the oxygen vacancy concentration. This is because the oxygen vacancies can form dangling bonds at the metal-oxygen sites, promoting the formation of M-OH on the catalyst surface.
[0061] In some embodiments, the iron salt is ferric chloride.
[0062] In some embodiments, the ratio of Co3O4 nanoparticles to polyol is 9 mg:4 mL.
[0063] In some embodiments, the polyol is at least one of ethylene glycol, diethylene glycol, and glycerol.
[0064] In some embodiments, the mass ratio of the chelating agent to the Co3O4 nanoparticles is 40:3.
[0065] In some embodiments, the chelating agent is at least one of trisodium citrate, sodium EDTA, and sodium tartrate.
[0066] In some embodiments, the mass ratio of the pH adjuster to the Co3O4 nanoparticles is 20:9.
[0067] In some embodiments, the pH adjuster is at least one of sodium acetate, ammonium hydroxide, sodium carbonate, sodium phosphate, and sodium borate.
[0068] In some embodiments, the solvothermal reaction is carried out at a temperature of 200° C. and for a time of 10 hours.
[0069] In some embodiments, Co3O4 nanoparticles are prepared by calcining a cobalt-based metal organic framework, wherein the calcination is carried out in an air atmosphere, the heating rate during the calcination process is 2.5°C / min, the calcination temperature is 550°C, and the calcination time is 4h.
[0070] In some embodiments, the cobalt-based metal-organic framework is a ZIF-67 material; the preparation method of the ZIF-67 material comprises the following steps: dissolving 2-methylimidazole and cobalt nitrate in methanol, respectively, to obtain a 2-methylimidazole solution and a cobalt nitrate solution, respectively; adding the 2-methylimidazole solution to the cobalt nitrate solution, stirring, standing, centrifuging, washing, and drying to obtain the ZIF-67 material.
[0071] In some embodiments, the molar ratio of cobalt nitrate to 2-methylimidazole is 1-8:1.
[0072] In a second aspect, the present invention further provides an oxygen-vacancy-rich cobalt oxide / ferroferric oxide composite catalyst, which is prepared by the preparation method in the first aspect.
[0073] In some embodiments, the oxygen-vacancy-rich cobalt oxide / ferroferric oxide composite catalyst includes cobalt oxide nanoparticles, the cobalt oxide nanoparticles include Co3O4 nanoparticles and CoO nanoparticles, and Fe3O4 nanoparticles are grown on the surface of the cobalt oxide nanoparticles.
[0074] In some embodiments, the mass ratio of cobalt to iron in the oxygen-rich vacancy cobalt oxide / ferroferric oxide composite catalyst is 0.2 to 5.0: 1. As an example, the mass ratio of cobalt to iron may be 0.2: 1, 0.3: 1, 0.4: 1, 0.6: 1, 0.8: 1, 1: 1, 1.2: 1, 1.5: 1, 2.0: 1, 2.6: 1, 3: 1, 3.4: 1, 4: 1, 4.3: 1, 4.8: 1, 5: 1, or any two of the above point values may be used as end values. Optionally, the mass ratio of cobalt to iron in the oxygen-rich vacancy cobalt oxide / ferroferric oxide composite catalyst is 0.5 to 4.0: 1. In the preparation method of the present invention, the selectivity of the catalyst for nitrate reduction reaction can be optimized by regulating the ratio of cobalt to iron in the composite catalyst. In the present invention, adding appropriate cobalt active sites can promote the hydrogenation reaction of nitrates, but excessive cobalt sites will enhance the hydrogen evolution reaction, thereby inhibiting nitrate reduction.
[0075] In a third aspect, the present invention further provides the use of the oxygen-rich vacancy cobalt oxide / ferroferric oxide composite catalyst of the second aspect in the electrocatalytic reduction of nitrate to synthesize ammonia.
[0076] In some embodiments, the method for using the oxygen-rich vacancy cobalt oxide / ferroferric oxide composite catalyst in the electrocatalytic reduction of nitrate to synthesize ammonia comprises the following steps:
[0077] (1) preparing a catalytic electrode by using an oxygen-vacancy-rich cobalt oxide / ferroferric oxide composite catalyst;
[0078] (2) constructing an electrocatalytic device using the catalytic electrode as the working electrode;
[0079] (3) The nitrate wastewater is introduced into an electrocatalytic device for electrocatalytic reduction reaction, thereby completing the treatment of the nitrate wastewater and collecting ammonia gas.
[0080] In some embodiments, in step (1), the method for preparing a catalytic electrode includes the following steps: mixing an oxygen-rich cobalt oxide / ferroferric oxide composite catalyst with a mixed solution of water, isopropanol and naphthol, ultrasonically dispersing the mixture, drop coating the mixture onto a conductive substrate, and drying the mixture to obtain a catalytic electrode.
[0081] In some embodiments, the ratio of the oxygen-vacancy-rich cobalt oxide / ferroferric oxide composite catalyst to the mixed solution of water, isopropanol and naphthol is 5 mg: 1 mL.
[0082] In some embodiments, the volume ratio of water, isopropanol and naphthol in the mixed solution of water, isopropanol and naphthol is 13:6:1.
[0083] In some embodiments, the oxygen vacancy-rich cobalt oxide / ferrosoferric oxide composite catalyst is mixed with a mixed solution of water, isopropanol and naphthol, and ultrasonically dispersed for 1 hour.
[0084] In some embodiments, the conductive substrate is conductive carbon paper.
[0085] In some embodiments, after the oxygen vacancy-rich cobalt oxide / ferrosoferric oxide composite catalyst is drop-coated, the conductive substrate is dried at a temperature of 50°C.
[0086] In some embodiments, in step (3), the concentration of nitrate in the nitrate wastewater is 0.01 mol / L to 0.1 mol / L.
[0087] In some embodiments, the nitrate is potassium nitrate.
[0088] In some embodiments, potassium hydroxide is added to the nitrate wastewater.
[0089] In some embodiments, the concentration of potassium hydroxide in the nitrate wastewater is 0.1 mol / L.
[0090] In some embodiments, the electrocatalytic reduction reaction is performed at an electrode potential of -0.3 V to -1.1 V relative to a reversible hydrogen electrode.
[0091] In some embodiments, the electrocatalytic reduction reaction time is 0.5 h.
[0092] In order to facilitate understanding of the innovation of the present invention, the present invention also provides the following specific examples. The materials and instruments used in the following examples are all commercially available.
[0093] Embodiment 1:
[0094] A method for preparing an oxygen-rich vacancy cobalt oxide / ferroferric oxide composite catalyst comprises the following steps:
[0095] S1. Provide a cobalt-based metal organic framework. Specifically, the cobalt-based metal organic framework used is a ZIF-67 material, wherein the preparation method of the ZIF-67 material comprises the following steps:
[0096] 8 mmol 2-methylimidazole and 2 mmol cobalt nitrate hexahydrate were dissolved in 50 mL methanol to obtain 2-methylimidazole solution and cobalt nitrate solution, respectively; the 2-methylimidazole solution was slowly added to the cobalt nitrate solution, stirred at room temperature for 12 hours, allowed to stand for 4 hours, the purple precipitate was collected, washed three times by centrifugation with methanol, and vacuum dried at 60°C for 12 hours to obtain ZIF-67 material.
[0097] S2. Place 300 mg of the ZIF-67 material prepared in step S1 in a covered corundum crucible, heat it to 550° C. at 2.5° C. / min in a muffle furnace for calcination, maintain for 4 hours, and cool it naturally to obtain Co3O4 nanoparticles.
[0098] S3, 90 mg of the Co3O4 nanoparticles prepared in step S2 were mixed with 40 mL of ethylene glycol, and ultrasonically dispersed, 0.4 g of ferric chloride hexahydrate was added to dissolve it in ethylene glycol to form a mixed solution, 1.2 g of trisodium citrate was added for coordination reaction, 0.2 g of anhydrous sodium acetate was added, and stirred for 1 h to obtain a precursor dispersion, and the obtained dispersion was transferred to a Teflon-lined autoclave, and a solvent thermal reaction was carried out at 200 ° C for 10 h. After the reaction was completed, the dispersion was centrifuged at 12000 rpm for 5 min, and the centrifuged product was washed with anhydrous ethanol, and the washing was repeated three times, and vacuum dried at 60 ° C for 10 h to obtain an oxygen-rich cobalt oxide / ferroferric oxide composite catalyst, recorded as CoO X / Fe3O4.
[0099] The oxygen-vacancy-rich cobalt oxide / ferroferric oxide composite catalyst prepared in Example 1 comprises cobalt oxide nanoparticles, wherein the cobalt oxide nanoparticles comprise Co3O4 nanoparticles and CoO nanoparticles, wherein Fe3O4 nanoparticles grow on the surface of the cobalt oxide nanoparticles.
[0100] The mass ratio of cobalt to iron in the oxygen-vacancy-rich cobalt oxide / ferroferric oxide composite catalyst prepared in Example 1 is 1.15:1.
[0101] Comparative Example 1:
[0102] A method for preparing a Co3O4 catalyst comprises the following steps:
[0103] (1) 8 mmol 2-methylimidazole and 2 mmol cobalt nitrate hexahydrate were dissolved in 50 mL methanol to obtain 2-methylimidazole solution and cobalt nitrate solution, respectively; the 2-methylimidazole solution was slowly added to the cobalt nitrate solution, stirred at room temperature for 12 hours, allowed to stand for 4 hours, the purple precipitate was collected, washed three times by centrifugation with methanol, and vacuum dried at 60°C for 12 hours to obtain ZIF-67 material.
[0104] (2) 300 mg of the ZIF-67 material prepared in step S1 was placed in a covered corundum crucible, and the temperature was raised to 550°C in a muffle furnace at a rate of 2.5°C / min for calcination, and the mixture was kept at that temperature for 4 h. After the temperature was naturally lowered, a Co3O4 catalyst was obtained, which was recorded as Co3O4.
[0105] Comparative Example 2:
[0106] A method for preparing a Fe3O4 catalyst comprises the following steps:
[0107] Weigh 0.4g of ferric chloride hexahydrate, 1.2g of trisodium citrate and 0.2g of anhydrous sodium acetate and add them to 40mL of ethylene glycol in sequence, stir for 1h to obtain a mixed solution. The mixed solution is transferred to a Teflon-lined autoclave, and subjected to a solvothermal reaction at 200°C for 10h. After the reaction is completed, centrifuge at 12000rpm for 5min, wash the centrifuged product with anhydrous ethanol, repeat the washing three times, and vacuum dry at 60°C for 10h to obtain a Fe3O4 catalyst, which is recorded as Fe3O4.
[0108] The catalysts prepared in Example 1 and Comparative Examples 1-2 were characterized, and the results were as follows:
[0109] Figure 1 The oxygen-rich cobalt oxide / ferroferric oxide composite catalyst (CoO X / Fe3O4), the Co3O4 catalyst (Co3O4) prepared in Comparative Example 1, and the Fe3O4 catalyst (Fe3O4) prepared in Comparative Example 2. Figure 1It can be seen that four obvious diffraction peaks appear at 31.3°, 36.9°, 59.4° and 65.2°, corresponding to the Co3O4 crystal planes (220), (311), (511) and (440), respectively. Fe3O4 has obvious diffraction peaks at 30.1°, 35.4°, 56.9° and 62.5°, which are basically consistent with the characteristic peaks of the standard card (JCPDS: 19-0629), which shows that Co3O4 nanoparticles participate in the solvent thermal reaction process. After adding ferric chloride, the diffraction intensity of Co3O4 decreases, and obvious new diffraction peaks appear at 36.5°, 42.4° and 61.5°, which is consistent with the standard card of CoO (JCPDS: 43-1004). It can be seen that the cobalt oxide in the catalyst prepared by the preparation method of the present invention includes Co3O4 and CoO.
[0110] In addition, as shown in Table 1, the mass ratio of Co / Fe in the oxygen vacancy-rich cobalt oxide / ferroferric oxide composite catalyst is 1.15.
[0111] Table 1 ICP-OES quantitative detection results of oxygen-rich cobalt oxide / ferroferric oxide composite catalyst prepared in Example 1
[0112]
[0113]
[0114] Figure 2 The oxygen-rich cobalt oxide / ferroferric oxide composite catalyst (CoO X / Fe3O4) SEM picture. Figure 2 It can be seen that in the present invention, after the ZIF-67 material is subjected to high-temperature oxidation calcination, due to the decomposition of the carbon and nitrogen skeletons, the Co3O4 nanoparticles spontaneously aggregate together to form irregular shapes. At the same time, after Ostwald ripening, Fe3O4 spheres grow on the irregular cobalt oxide surface, and there is no obvious stacking between the nanoparticles, which provides many active sites for surface catalytic reactions.
[0115] Figure 3 The oxygen-rich cobalt oxide / ferroferric oxide composite catalyst (CoO X / Fe3O4), the Co3O4 catalyst (Co3O4) prepared in Comparative Example 1, and the Fe3O4 catalyst (Fe3O4) prepared in Comparative Example 2. Figure 3 It can be seen that three typical peaks can be seen in the O1s spectrum, namely 529.9eV lattice oxygen (O L ), 531.6eV oxygen defect (O V) and 533.2eV for the surface adsorption of hydroxyl groups (-OH). By comparing the oxygen vacancy peak area and the O1s peak area, the percentage of oxygen defects in oxygen species can be determined. X / Fe3O4 and Fe3O4, the proportions of oxygen vacancies are 31.8%, 42.0% and 36.5%, respectively, which indicates that CoO X / Fe3O4 has the highest concentration of oxygen vacancies. In addition, the content of -OH adsorbed on the catalyst surface increases with the increase of oxygen vacancy concentration, because oxygen vacancies can form dangling bonds at metal-oxygen sites, promoting the formation of M-OH on the catalyst surface.
[0116] EPR can provide specific signals of unpaired electrons in materials and is therefore further used to identify the presence of oxygen vacancies. Figure 4 shown. Figure 4 The oxygen-rich cobalt oxide / ferroferric oxide composite catalyst (CoO X / Fe3O4), the Co3O4 catalyst (Co3O4) prepared in Comparative Example 1, and the Fe3O4 catalyst (Fe3O4) prepared in Comparative Example 2. Figure 4 It can be seen that the signal of g = 2.003 is due to the oxygen vacancies in the sample capturing electrons, which strongly proves the existence of oxygen vacancies in the sample. X / Fe3O4 exhibits the highest EPR signal intensity, indicating the presence of the highest concentration of oxygen vacancies.
[0117] Example 2
[0118] An application of an oxygen-rich vacancy cobalt oxide / ferroferric oxide composite catalyst in electrocatalytic reduction of nitrate to synthesize ammonia, specifically using the oxygen-rich vacancy cobalt oxide / ferroferric oxide composite catalyst prepared in Example 1 to prepare a catalytic electrode and perform an electrocatalytic reduction reaction on nitrate wastewater, comprising the following steps:
[0119] (1) The oxygen-vacancy-rich cobalt oxide / ferroferric oxide composite catalyst is made into a catalytic electrode, specifically:
[0120] 5 mg of the oxygen-rich cobalt oxide / ferroferric oxide composite catalyst prepared in Example 1 was mixed with 1 mL of a mixed solution of water, isopropanol and naphthol, and ultrasonically dispersed for 1 h to form a uniform ink. 100 μL of the ink was drop-coated on a conductive carbon paper (with an area of 0.25 cm 2 ) and dried at 50° C. to obtain a catalytic electrode. In this step, the volume ratio of water, isopropanol and naphthol in the mixed solution of water, isopropanol and naphthol is 13:6:1.
[0121] (2) Using the catalytic electrode as the working electrode, constructing an electrocatalytic device, specifically:
[0122] The catalytic electrode prepared in step (1) is used as a working electrode, a counter electrode is a platinum sheet, and a reference electrode is silver / silver chloride, which are placed in an electrolytic cell to construct a three-electrode system, and connected to an electrochemical workstation to obtain an electrocatalytic device. In the device, the electrolytic cell is an H-type electrolytic cell, and a Nafion 117 proton exchange membrane is used to separate the positive and negative electrolytes, wherein the electrolyte in the anode chamber is 0.1M KOH.
[0123] (3) The nitrate wastewater was introduced into an electrocatalytic device for electrocatalytic reduction reaction, specifically, 30 mL of a mixed solution of 0.1 mol / L potassium hydroxide and 0.1 mol / L potassium nitrate was introduced into the cathode chamber of the electrocatalytic device, and the electrocatalytic reduction of nitrate to synthesize ammonia was tested at an electrode potential of -0.3 V to -1.1 V relative to the reversible hydrogen electrode using the chronoamperometry of the electrochemical workstation, and the reaction time was 0.5 h. In this step, argon gas was continuously introduced into the cathode electrolyte for 30 min before the test to remove impurity gases.
[0124] Control group: The catalyst prepared in Comparative Example 1 and Comparative Example 2 was used to replace the catalyst in Example 1 to prepare a catalytic electrode, and an electrocatalytic reduction reaction was carried out under the same conditions.
[0125] During the test, a certain amount of the electrolyte after the reaction was taken and the concentrations of nitrate, nitrite and ammonia nitrogen in the electrolyte were determined by spectrophotometry. The Faraday current efficiency (FE) of the catalyst for electrocatalytic reduction of nitrate to synthesize ammonia can be calculated by equations (1) and (2): NH3 ) and ammonia production rate (Yieid NH3 ).
[0126] FE NH3 =(8F×C NH3 ×V) / M NH3 ×Q (1),
[0127] Yield NH3 =(C NH3 ×V) / (M NH3 ×t×S) (2).
[0128] In the above formula, F is the Faraday constant, 96485C / mol; C is the mass concentration of ammonia nitrogen; V is the volume of the cathode electrolyte; M is the molar mass of ammonia nitrogen; Q is the reaction charge; t is the reaction time; S is the geometric area of the working electrode.
[0129] Figure 5 The oxygen-rich cobalt oxide / ferroferric oxide composite catalyst (CoO X / Fe3O4), Co3O4 catalyst (Co3O4) and Fe3O4 catalyst (Fe3O4) at different potentials.
[0130] Figure 6 The oxygen-rich cobalt oxide / ferroferric oxide composite catalyst (CoO X / Fe3O4), Co3O4 catalyst (Co3O4) and Fe3O4 catalyst (Fe3O4) at different potentials.
[0131] Depend on Figure 5 and Figure 6 It can be seen that compared with Co3O4) and Fe3O4, the oxygen-rich cobalt oxide / ferroferric oxide composite catalyst (CoO X / Fe3O4) has high reactivity and selectivity for nitrate reduction to synthesize ammonia.
[0132] In this example, the oxygen-rich cobalt oxide / ferrous oxide composite catalyst (CoO X The electrocatalytic reduction effect of the catalytic electrode made of 2-nitrogen / Fe3O4) on nitrate wastewater with different concentrations at a potential of -0.9 V is shown in the following figure. Figure 7 shown.
[0133] Figure 7 The oxygen-rich cobalt oxide / ferroferric oxide composite catalyst (CoO X The comparison chart of the Faraday current efficiency and ammonia production rate of the catalytic electrode made of / Fe3O4) for nitrate wastewater with different concentrations at a potential of -0.9V. Figure 7 It can be seen that in the present invention, the oxygen-rich cobalt oxide / ferroferric oxide composite catalyst (CoO X / Fe3O4) was used for electrocatalytic reduction of nitrate wastewater with different concentrations. The ammonia production rate and the Faraday current efficiency increased with the increase of nitrate concentration, indicating that there is a certain competition between nitrate reduction reaction and hydrogen evolution reaction.
[0134] In this example, the oxygen-rich cobalt oxide / ferrous oxide composite catalyst (CoO X The electrocatalytic reduction effect of the catalytic electrode made of 200 μg / cm2 / Fe3O4) on nitrate wastewater with a concentration of 0.01 mol / L at a potential of -0.9 V was studied. Figure 8 shown.
[0135] Figure 8 The oxygen-rich cobalt oxide / ferroferric oxide composite catalyst (CoO X / Fe3O4) under different electrocatalytic reduction reaction conditions. Figure 8 The curves of nitrate, nitrite and ammonia nitrogen changing during the electrocatalytic reaction are further shown. Figure 8 It can be seen that within 5h, CoO X The conversion rate of / Fe3O4 to 0.01mol / L nitrate is 98.45%, the conversion rate of ammonia nitrogen is 75.20%, and the conversion rate of nitrite is 0.60%, which shows that the catalyst has good selectivity.
[0136] In this example, the oxygen-rich cobalt oxide / ferrous oxide composite catalyst (CoO X The catalytic electrode made of 2-(4-(2-Fe3O4)) was used to treat the nitrate wastewater with a concentration of 0.1 mol / L at a potential of -0.9 V. The results are as follows: Fig. 9 shown.
[0137] Fig. 9 The oxygen-rich cobalt oxide / ferroferric oxide composite catalyst (CoO X / Fe3O4) on the recycling treatment effect of nitrate wastewater. Fig. 9 The decay of the ammonia production rate and Faraday current efficiency of the catalyst within 10 cycles is shown in Figure 2. Fig. 9 The results show that after 10 cycles, CoO X / Fe3O4 ammonia production rate decreased by only 7.39%, and the ammonia production Faraday current efficiency decreased by only 4.94%, indicating that CoO X / Fe3O4 has good stability under alkaline conditions.
[0138] The above results show that, compared with the cobalt oxide catalyst prepared by the conventional method, the oxygen-vacancy-rich cobalt oxide / ferroferric oxide composite catalyst prepared by the present invention contains abundant oxygen vacancies, which can not only significantly enhance the adsorption and activation ability of nitrate, but also significantly improve the selectivity and reaction rate of synthetic ammonia. The ammonia production rate of the oxygen-vacancy-rich cobalt oxide / ferroferric oxide composite catalyst of the present invention is 1.09 mmol h -1 cm -2 , the Faraday current efficiency is 82.22%, and the ammonia nitrogen selectivity is 75.2%. The oxygen-vacancy-rich cobalt oxide / ferroferric oxide composite catalyst of the present invention has the characteristics of being rich in oxygen vacancies, and can enhance the adsorption and activation ability of nitrates, so that high-efficiency electrocatalytic reduction of nitrates can be achieved, and at the same time, it also has very excellent stability, and has important application value in nitrate wastewater treatment and ammonia synthesis.
[0139] The above is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as above in the preferred embodiment, it is not used to limit the present invention. Any technician familiar with the art can make many possible changes and modifications to the technical solution of the present invention by using the methods and technical contents disclosed above without departing from the spirit and technical solution of the present invention, or modify it into an equivalent embodiment of equivalent changes. Therefore, any simple modification, equivalent replacement, equivalent change and modification made to the above embodiments according to the technical essence of the present invention without departing from the content of the technical solution of the present invention, still fall within the scope of protection of the technical solution of the present invention.
Claims
1. A method for preparing an oxygen-rich vacancy cobalt oxide / ferroferric oxide composite catalyst, characterized in that: The following steps are involved: S1, mixing Co3O4 nanoparticles with polyols, dispersing by ultrasonication, adding iron salt, dissolving, adding a chelating agent for coordination reaction, and obtaining a mixed solution; S2. The mixed solution is subjected to a solvothermal reaction with a pH regulator to obtain an oxygen-rich vacancy cobalt oxide / ferroferric oxide composite catalyst.
2. The preparation method according to claim 1, characterized in that: The mass ratio of the iron salt to the Co3O4 nanoparticles is 1-14:
1.
3. The preparation method according to claim 2, characterized in that: The iron salt is ferric chloride; the ratio of the Co3O4 nanoparticles to the polyol is 9 mg:4 mL; the polyol is at least one of ethylene glycol, diethylene glycol, and propylene glycol; the mass ratio of the chelating agent to the Co3O4 nanoparticles is 40:3; the chelating agent is at least one of trisodium citrate, sodium ethylenediaminetetraacetate, and sodium tartrate; the mass ratio of the pH regulator to the Co3O4 nanoparticles is 20:9; the pH regulator is at least one of sodium acetate, ammonium hydroxide, sodium carbonate, sodium phosphate, and sodium borate.
4. The preparation method according to claim 2, characterized in that: The temperature of the solvent thermal reaction is 200° C.; the time of the solvent thermal reaction is 10 hours.
5. The preparation method according to any one of claims 1 to 4, characterized in that: The Co3O4 nanoparticles are prepared by calcining a cobalt-based metal organic framework; the calcination is carried out in an air atmosphere; the heating rate during the calcination is 2.5°C / min; the calcination temperature is 550°C; and the calcination time is 4h; The cobalt-based metal organic framework is a ZIF-67 material; the preparation method of the ZIF-67 material comprises the following steps: dissolving 2-methylimidazole and cobalt nitrate in methanol respectively to obtain a 2-methylimidazole solution and a cobalt nitrate solution respectively; adding the 2-methylimidazole solution to the cobalt nitrate solution, stirring, standing, centrifuging, washing, and drying to obtain the ZIF-67 material; the molar ratio of the cobalt nitrate to the 2-methylimidazole is 1 to 8:
1.
6. An oxygen-rich vacancy cobalt oxide / ferroferric oxide composite catalyst, characterized in that: The oxygen-vacancy-rich cobalt oxide / ferroferric oxide composite catalyst is prepared by the preparation method described in any one of claims 1 to 5.
7. The oxygen-rich vacancy cobalt oxide / ferroferric oxide composite catalyst according to claim 6, characterized in that: The oxygen-rich vacancy cobalt oxide / ferroferric oxide composite catalyst comprises cobalt oxide nanoparticles; the cobalt oxide nanoparticles comprise Co3O4 nanoparticles and CoO nanoparticles; Fe3O4 nanoparticles grow on the surface of the cobalt oxide nanoparticles; the mass ratio of cobalt to iron in the oxygen-rich vacancy cobalt oxide / ferroferric oxide composite catalyst is 0.2 to 5.0:
1.
8. Use of the oxygen-vacancy-rich cobalt oxide / ferroferric oxide composite catalyst as claimed in claim 6 or 7 in electrocatalytic reduction of nitrate to synthesize ammonia.
9. The use according to claim 8, characterized in that: The following steps are involved: (1) preparing a catalytic electrode by using an oxygen-vacancy-rich cobalt oxide / ferroferric oxide composite catalyst; (2) constructing an electrocatalytic device using the catalytic electrode as the working electrode; (3) The nitrate wastewater is introduced into an electrocatalytic device for electrocatalytic reduction reaction, thereby completing the treatment of the nitrate wastewater and collecting ammonia gas.
10. The use according to claim 9, characterized in that: In step (1), the preparation method of the catalytic electrode comprises the following steps: mixing the oxygen-rich vacancy cobalt oxide / ferroferric oxide composite catalyst with a mixed solution of water, isopropanol and naphthol, ultrasonically dispersing, drop-coating on a conductive substrate, and drying to obtain a catalytic electrode; the ratio of the oxygen-rich vacancy cobalt oxide / ferroferric oxide composite catalyst to the mixed solution of water, isopropanol and naphthol is 5 mg: 1 mL; the volume ratio of water, isopropanol and naphthol in the mixed solution of water, isopropanol and naphthol is 13: 6: 1; the ultrasonic dispersion time is 1 hour; the conductive substrate is conductive carbon paper; the drying temperature is 50°C; In step (3), the concentration of nitrate in the nitrate wastewater is 0.01 mol / L to 0.1 mol / L; the nitrate is potassium nitrate; potassium hydroxide is added to the nitrate wastewater; the concentration of potassium hydroxide in the nitrate wastewater is 0.1 mol / L; the electrocatalytic reduction reaction is carried out at an electrode potential of -0.3 V to -1.1 V relative to the reversible hydrogen electrode; and the time of the electrocatalytic reduction reaction is 0.5 h.
Citation Information
Cited By
Device and method for treating cadmium ions in wastewater through electrochemical adsorption
CN121063656A